Role Of Parenting Dalam Menanggulangi Digresi Gadget Pada Anak - Kholil, Muhammad; Rozi, Fathor; Azizah, Ella Shofiatun (Jurnal Ilmiah Mandala Education (JIME), 2023)
The purpose of this study was to describe the role of parents in responding to gadgets and their implicit behavior towards children in Pakistaji village, Wonoasih sub-district, Probolinggo city with continuous control and orgrib Koran organizations (GMM) as shields for children. deviant behavior in children. The method used is descriptive qualitative with a case study type approach. Data collection was carried out through observation, interviews, and supported by documentation. This research was conducted in Pakistaji Village, Wonoasih District, Probolinggo City. The subjects in the study were parents and some children who depend on gadgets. The results of this study are the following: The frequency of using gadgets needs to be limited. Children don't need too many gadgets, because the most important thing is that children can use them and know how to use them optimally. Excessive intensity of using gadgets can trigger irregularities. The role of parents in responding to the use of gadgets in their children is very important. This is done so that children do not abuse their parents' trust in them. The attitude that needs to be shown is to accompany children when playing gadgets and parents must be able to operate them. As for the consequences if parents do not supervise the use of gadgets on their children, then their children will engage in deviant behavior. Forms of deviation in the form of attitudes and speech that are not good. Usually in the form of erotic attitudes and dirty words.The purpose of this study was to describe the role of parents in responding to gadgets and their implicit behavior towards children in Pakistaji village, Wonoasih sub-district, Probolinggo city with continuous control and orgrib Koran organizations (GMM) as shields for children. deviant behavior in children. The method used is descriptive qualitative with a case study type approach. Data collection was carried out through observation, interviews, and supported by documentation. This research was conducted in Pakistaji Village, Wonoasih District, Probolinggo City. The subjects in the study were parents and some children who depend on gadgets. The results of this study are the following: The frequency of using gadgets needs to be limited. Children don't need too many gadgets, because the most important thing is that children can use them and know how to use them optimally. Excessive intensity of using gadgets can trigger irregularities. The role of parents in responding to the use of gadgets in their children is very important. This is done so that children do not abuse their parents' trust in them. The attitude that needs to be shown is to accompany children when playing gadgets and parents must be able to operate them. As for the consequences if parents do not supervise the use of gadgets on their children, then their children will engage in deviant behavior. Forms of deviation in the form of attitudes and speech that are not good. Usually in the form of erotic attitudes and dirty words.